A STUDY OF KING AJATASATTU’S ROLE IN SUPPORTING BUDDHISM - อินทองปาน ประเวศ; วิศาลชัยธรรม พระครู; ฐานิสฺสโร พระมหาสมปอง (Journal of MCU Nakhondhat, 2015)
This research “A study of king Ajatasattu’s role in supporting Buddhism”, focused on three main issues: 1. to study a social context in the reign of king Ajatasattu, 2. to study the history of king Ajatasattu and 3. to study king Ajatasattu’s role in supporting Buddhism. These are by method of documentary researches. The research results found that: A social context in the reign of king Ajatasattu had variety, development and prosperity, including political systems and government in various models by dividing governmental areas in to sixteen big territories and five small ones; and they had the kings who ruled over them supremely. His history was that king Ajatasattu was the son of king Pimpisala and queen Vedehirajadevi. He ruled over the territory of Magada, succeeding from his father. Due to killing his father, king Ajatasattu repaid his previous action in the hell of Lohagumpi. When he was released from such action, he would become a private Buddha named Jivitavisesa. For his role in supporting Buddhism, after king Ajatasattu has visited the Buddha and proclaimed himself as one devoted to the Buddha, he firmly established in the Triple Gem throughout his life. He restored the dwelling places of eighteen monasteries and supported the first council convocation successfully; and also he constructed the stupa for containing the Buddha’s relics and its celebration was greatly held. From his role in supporting Buddhism Teaching temporalities, personal temporalities, material temporalities and ritual temporalities with his utmost effort in order to get his people to reach their lives according to the Buddhadhamma – the Buddha’s teachings. These could be said that it was the stable foundation and helped support Buddhism flourish afterwards.